Pengaruh Current Ratio (CR), Return on Asset (ROA), Return on Equity (ROE) Terhadap Harga Saham pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Wildan, Alfan Hoirul; Maithy, Sifera Patricia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
Manufacturing companies in the food and beverage sub-sector must improve their performance in managing capital invested by shareholders to ensure that all assets are utilized optimally to generate maximum profits. Investors generally assume that a higher stock price reflects a greater ability of the company to generate earnings, which in turn increases the attractiveness of its shares. This study aims to examine the effect of Current Ratio (CR), Return on Assets (ROA), and Return on Equity (ROE) on stock prices. The research focuses on 26 food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The analytical method used is multiple linear regression, supported by the t-test for partial regression coefficients at a 5% significance level, along with classical assumption tests, including normality, multicollinearity, and autocorrelation tests. The results show that only ROE has a significant influence on stock prices, while CR and ROA have no significant effect.